Evaluation of self-healing in concrete using linear and nonlinear resonance spectroscopy. (13th June 2022) - Kim, Ryulri; Woo, Ukyong; Shin, Myoungsu; Ahn, Eunjong; Choi, Hajin
Highlights: Self-healing in concrete were investigated using linear and nonlinear linear and nonlinear resonance techniques. Specimens incorporating self-healing capsules shows better performance than specimens with SCMs. Linear resonance frequency exhibited a strong correlation with the closures of the external crack area. Nonlinear acoustic parameter showed a week correlation with the closures of external crack area. Abstract: In this study, self-healing in concrete incorporating two types of healing agents, i.e., 1) a self-healing capsule and 2) supplementary cementitious materials with crystalline admixtures, is monitored using linear and nonlinear resonance acoustic spectroscopy techniques. Beam-shaped concrete specimens are prepared using the healing agents, and after 28 days, a single vertical crack with a width ranging from 0.25 to 0.35 mm is generated at the center of the specimens. To monitor the self-healing process in concrete, the samples are vibrated via impact-based excitation methods in the flexural and longitudinal directions, whereas the linear resonance frequency and acoustic nonlinearity parameter α are measured for two months. Additionally, the acoustic nonlinearity parameter is analyzed using two different methods: 1) multiple impacts with manually controlled amplitude, and 2) single impact with artificially controlled amplitude by changing the windowing region in a signal. Test results show that the linear resonance frequency increases up to 86%–97% that of the uncracked condition after 63 days of self-healing. The linear trend of the resonance frequency is correlated significantly with the decrease in the external crack area, but the change in α is affected by the presence of partially filled cracks than by the overall crack area.